THE MILITARY IN VIETNAM'S FEUDAL SOCIETY: A STUDY OF THE LOCAL MILITIA UNDER THE NGUYỄN DYNASTY’S POLICY OF "LODGING SOLDIERS AMONG FARMERS" (1802-1885) - Ngo Duc Chi; Ngo Duc Lap (Romanian Journal of Historical Studies)
This paper focuses on clarifying the role of local militia, a crucial force in the policy of “lodging soldiers among farmers” under the Nguyen Dynasty. To elucidate this issue, the author employs two primary research methods in history: historical and logical approaches. The historical method aids in reconstructing the historical picture as objectively as possible, while the logical method facilitates the author in making assessments and evaluations of the objective laws governing the research problem. The research materials used by the author are valuable primary sources from the Nguyen Dynasty that have been preserved to this day. Additionally, the author leverages the research of other scholars to clarify the raised issues. Through this, the paper will clarify specific issues as follows: First, the author will provide a general overview of the local militia under the Nguyen Dynasty; Second, the paper will elucidate the contributions of the local militia under the Nguyen Dynasty; Third, the paper will evaluate the role of the local militia in the “lodging soldiers among farmers” policy of the Nguyen Dynasty (1802-1885). The results of this study will serve as a valuable source for clarifying the human resource management of the Nguyen feudal dynasty (1802-1885). Moreover, it is essential material for those interested in this subject.